2001
DOI: 10.1046/j.0007-1323.2001.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of atypical symptoms of gastro-oesophageal reflux to antireflux surgery

Abstract: Atypical symptoms of GOR are improved by fundoplication, but symptom resolution occurs in fewer than 50 per cent of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 25 publications
6
35
1
2
Order By: Relevance
“…The long-term amelioration of supraesophageal symptoms after a LNF in our study was found in 61% of the patients and only 8% of the patients suffered from difficult or severe cough or hoarseness comparing favorably to some other reported results [12,26]. The symptomatic outcome of patients in this study supports the more promising results of other studies on patients with extraesophageal symptoms as the main indication for LNF [16,18,27,28,29].…”
Section: Discussionsupporting
confidence: 81%
“…The long-term amelioration of supraesophageal symptoms after a LNF in our study was found in 61% of the patients and only 8% of the patients suffered from difficult or severe cough or hoarseness comparing favorably to some other reported results [12,26]. The symptomatic outcome of patients in this study supports the more promising results of other studies on patients with extraesophageal symptoms as the main indication for LNF [16,18,27,28,29].…”
Section: Discussionsupporting
confidence: 81%
“…The same holds true for extra-esophageal manifestations which are less responsive to ARS than typical symptoms ( fig. 7) [99].…”
Section: Long-term Managementmentioning
confidence: 99%
“…Outcome of heartburn and extra-esophageal symptoms after anti-reflux surgery. Adapted from Farrell et al [99].…”
Section: Long-term Managementmentioning
confidence: 99%
“…LARS prevents vocal fold chemical irritation caused by the blockage of acidic reflux which is thought to accelerate the decreases in erythema/hyperemia and subglottic and vocal fold edema, which is relatively reversible [25][26][27]. The reversible mucosal change may also promote improvement of the voice symptom-related (RSI, VHI-10) and GRBAS scale scores.…”
Section: Discussionmentioning
confidence: 93%
“…So et al found a 93 % improvement in the typical complaints of GERD following fundoplication, but only a 56 % improvement for atypical complaints [24]. Farrel et al found postsurgical improvement in 99 %, with complete resolution in 87 % of patients with predominant symptoms of GERD, and 93 % and 48 % improvement and resolution for patients in whom LPR symptoms were predominant [25]. In our study, the rate of regression of atypical symptoms was lower: globus and throat clearing in 23.1 %, irritating cough in 12.3 %.…”
Section: Discussionmentioning
confidence: 95%